Small and medium enterprises in Muslim countries - Abdullah, Moha Asri (IIUM Press, 2015)
The development and prosperity of Small and Medium Enterprises (SMEs) is crucial to the development agenda of any economy in the world, be it in developed or developing countries alike. This is especially so for Muslim countries, most of which fall under low income countries. Nonetheless, the work on small and medium enterprises (SMEs) in Muslim countries is hardly made available. In realising it, this book provides an overall account of small and medium enterprises in some selected Muslim countries, namely Turkey, Nigeria, Malaysia, Indonesia, Iran, Pakistan, Jordan, Tunisia and Bangladesh. All the selected countries have made the development of SMEs a priority since they contribute immensely to their economic development. Thus, this book provides a review of the experiences, issues and challenges, incentives and policies adopted, prospects for growth and development of SMEs in these countries. Overall, the book is divided into two main parts. The first part presents the overall roles and contributions of SMEs, problems, developments and challenges of SMEs in the selected Muslim countries. This part features chapters on Turkey, Nigeria, Malaysia, Indonesia, Iran, Pakistan, and Bangladesh. Second part focuses on some specific issues of SMEs in Muslim countries, including finance, legal, linkages, networking, e-commerce and the Islamic perspective of SMEs.